Health and income inequality: a comparative analysis of USA and Italy - La Porta, Caterina A. M.; Zapperi, Stefano (Frontiers in Public Health, 2024)
Socio-economic background is often an important determinant for health with low income households having higher exposure to risk factors and diminished access to healthcare and prevention, in a way that is specific to each country. Here, we perform a comparative analysis of the relations between health and income inequality in two developed countries, USA and Italy. We exploit longitudinal and cross-sectional data from surveys to show that the income class determines the incidence of chronic pathologies, associated risk-factors and psychiatric conditions, but find striking differences in health inequality between the two countries. We then focus our attention on a fraction of very disadvantaged households in the USA whose income in persistently at the bottom of the distribution over a span of 20 years and which is shown to display particularly dire health conditions. Low income people in the USA also display comorbidity patterns that are not found in higher income people, while in Italy income appears to be less relevant for comorbidity. Taken together our findings illustrate how differences in lifestyle and the healthcare systems affect the health inequality.